Development of a highly thermostable immunoassay based on a nanobody-alkaline phosphatase fusion protein for carcinoembryonic antigen detection - Lin, Jingtao; Yu, Jianli; Wang, Huan; Xu, Yanru; Li, Fei; Chen, Xiaoheng; Liang, Yunlong; Tang, Jinsong; Wu, Lili; Zhou, Zhengwei; Chen, Cailing; Liu, Minjuan; et al. (Analytical and bioanalytical chemistry, 2020)
Carcinoembryonic antigen–related cell adhesion molecule 5 (CEACAM-5) assays are employed in routine clinical settings to diagnose tumor. We selected two nanobodies with high-affinity to CEACAM-5, termed Nb11C12 and Nb2D5, using phage-display technology. The Nb2D5 fused with calf intestinal alkaline phosphatase (CAP), human placental alkaline phosphatase (HAP), or Pyrococcus abyssi alkaline phosphatase (PAP) were expressed in human embryonic kidney (HEK293) cells. The enzymatic activity of Nb2D5-HAP fusion protein was the best and remained stable at 60 °C for 7 days. The affinity of Nb2D5-HAP fusion protein to CEACAM-5 reached 42 pM. A chemiluminescent enzyme immunoassay (CLEIA) based on Nb2D5-HAP fusion protein was established for quantitative CEACAM-5 assay in clinical settings. The CLEIA exhibited a wide linear range of 0.31–640 ng/mL toward CEACAM-5, with a limit of detection (LOD) of 0.85 ng/mL. No cross-reactivity occurred with CEACAM-1, CEACAM-3, CEACAM-6, or CEACAM-8, and no interference was observed with rheumatoid factors. The CLEIA based on Nb2D5-HAP fusion protein was stable for 8 weeks at 37 °C and 50% relative humidity. The CLEIA developed from Nb2D5-HAP fusion protein had much better stability and linearity with similar reproducibility compared with the enzyme-linked immunosorbent assay developed from conventional monoclonal antibodies, which have been widely used in clinics over the past several decades. Graphical abstract